Non-Reentrant Fascicular Tachycardia: Clinical and Electrophysiological Characteristics of a Distinct Type of Idiopathic Ventricular Tachycardia. (October 2016) - Talib, Ahmed Karim; Nogami, Akihiko; Morishima, Itsuro; Oginosawa, Yasushi; Kurosaki, Kenji; Kowase, Shinya; Komatsu, Yuki; Kuroki, Kenji; Igarashi, Miyako; Sekiguchi, Yukio; Aonuma, Kazutaka
Abstract : Background—: The most common form of idiopathic Purkinje-related ventricular tachycardia (VT) is the reentrant type. We describe the clinical and electrophysiological characteristics of focal non-reentrant fascicular tachycardia. Methods and Results—: Among 530 idiopathic VT patients who were referred for ablation, we identified 15 (2.8%) with non-reentrant fascicular tachycardia (11 men, 45±21 years). Sinus rhythm ECG showed normal conduction intervals with a His–ventricular interval of 41±4 ms. All patients had monomorphic VT (cycle length: 337±88 ms) with a relatively narrow QRS (123±12 ms), and they did not respond to verapamil during the initial presentation. VT exhibited right bundle-branch block/superior axis configuration in 11 patients (73%) and inferior axis in 3 (20%). In 1 patient (7%), VT exhibited left bundle-branch block/superior axis configuration. During ablation, spontaneous VT occurred in 3 patients (20%) and nonentraintable VT or identical premature ventricular complex was induced in 9 (60%). A high-frequency presystolic Purkinje potential was recorded during VT/premature ventricular complex, preceding the QRS by 25±16 ms. VT recurrence was observed in 4 patients (27%), and among them, 3 underwent pacemap-guided ablation during the first session. A second ablation with activation mapping guidance eliminated the VT during the 88±8-month follow-up. Conclusions—: Among idiopathic VT cases referred for ablation, 2.8% were focal non-reentrant fascicular tachycardia, which had distinct clinical characteristics and usually originated from the left posterior fascicle, and less commonly from the left anterior fascicle and right ventricular Purkinje network. Catheter ablation is effective, whereas pacemap-guided approach is less efficacious.